Integrating Local Culture And Ethnoscience In Manggarai-Based Stem Education To Enhance Science Literacy And Scientific Attitudes In The 21st Century - Wahyu, Yuliana; Edu, Ambros Leonangung; M. Taklal, Rei Stefen (Jurnal Ilmu Pendidikan, 2025)
Science learning that has been applied so far, especially in science learning in elementary school students, has not integrated culture (ethnoscience). This makes the understanding of science very low. This study aims to analyze the influence of ethnoscience-based STEM approaches in the context of Manggarai culture on science literacy and scientific attitudes of elementary school students in Lamba Leda District. This goal was achieved by conducting an experimental study on the integration of ethnoscience-based STEM in the context of Manggarai culture to improve students' literacy and scientific attitudes and using control groups as a comparator. Statistical analysis used a multivariate variance analysis test. The results of the analysis of students' science literacy data showed a value of F = 7.513 (P < 0.05), then H0 was rejected. This means that there is a significant difference in students' science literacy in the experimental class and the control class. The results of the analysis of scientific attitude data showed that the value of F = 27,725 (P < 0.05), then H0 was rejected. The results of this effectiveness test show that the application of ethnoscience-based STEM approaches in the context of Manggarai culture can improve the literacy and scientific attitude of elementary school students.